Pengaruh Pembiayaan Murabahah, Mudharabah, dan Musyarakah Terhadap Profitabilitas Bank BCA Syariah Periode 2018-2022 - Dio Nurrohman Gunawan; Dailibas Dailibas (Peneliti.net, 2023)
The economic instability sweeping the world has led to a slowdown in economic growth. One of the industries that contributes greatly to encouraging economic growth is the banking sector, both conventional banks and Islamic banks. In practice, BCA Syariah annual financial statements show an increase in the amount of murabahah, mudharabah and musyarakah financing from year to year, indicating that this type of financing continues to attract public interest. This study aims to determine the effect of murabahah, mudharabah and musyarakah financing on profitability by using ROA as a dependent variable. The method used in this study is descriptive with a quantitative approach. Samples were taken by the nonprobability method using purposive sampling. The data used in this study was obtained from the official website of BCA Syariah, OJK, and other relevant sources. The results of multiple linear regression analysis show that partially, murabahah financing has an insignificant effect on profitability, mudharabah financing has no significant effect on profitability, and musyarakah financing has a significant effect on profitability. For simultaneous test results showed the influence exerted from all three types of financing on the level of profitability.